Kemasan Pembelajaran Bahasa Arab Berbasis Teori Antropolinguistik Modern - Muhammad Yusuf; Eka Dewi Rahmawati (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2019)
Some Arabic learning at this time does not pay close attention to the study of Arabic culture. Learn in class only while learning theoretically calm language itself. Meanwhile, discussions about culture in learning are carried out in important ways. This second thing can be done so that it must be done by going hand in hand. Everything that is found in language contains original culture, and so culture is one that language cannot make. Macrolinguistic has become one of the scientific trends in studying the issue of learning Arabic in Indonesia. One of that dialogues in applied linguistics is anthropolinguistics. That scientific interdiscipline is the result of integration between culture and language. A significant relationship between language and culture makes academics interested in formulating the framework, so that it can be used as a basis for language studies through culture or cultural studies through language. In the modern era, anthropolinguistics has three theories, namely performance, indexicality, and participation. This paper examines how anthropolinguistic theory plays a role in learning Arabic in Indonesia, especially with regard to core competencies in it. This study uses a literature paradigm that is operationally obtained by author from books and articles that have relevance to the topic of discussion. Furthermore, the library data will be dialogue by the author systematically, objectively, and comprehensively. Analysis of the literature that has been done produce a synthesis that learning Arabic in the perspective of modern antropolinguis should consist of the following competencies, namely the grammatical competence, communicative competence and pragmatic, and Arabic language skills. From this theoretical study of anthropolinguistic learning based Arabic, it can be synthesized that the anthropolinguistic theory in Arabic learning has implications for its hard core in the learning process which cannot be denied at all. The hard core is related to the competencies that must be presented by an Arabic learner, especially in Indonesia, namely grammatical competence, communicative and pragmatic competence, and Arabic language skills.